Adaptive Hybrid ARQ (A-HARQ) for Ultra-Reliable Communication in 5G - Cabrera, Emerson; Gengfa Fang; Vesilo, Rein (2017 IEEE 85th Vehicular Technology Conference (VTC Spring), 2017)
In this paper, we address the need for motivating applications, such as mission critical industrial control and medical applications, to operate under the Ultra-Reliable Communication (URC) mode in the future 5th Generation (5G) cellular wireless networks, while also under strict Quality of Service (QoS) constraints such as ultra-low latency. Reliability has been shown to improve by using Hybrid Automatic Repeat reQuest (HARQ) for the retransmission (RTX) of erroneous packets during poor channel conditions. However, this can increase the delay to unacceptable levels if more than 1 RTX is required. Thus, an Adaptive HARQ (A-HARQ) scheme is proposed, where RTX are done on better quality sub-bands, with resources dynamically allocated based on Channel Quality Indicator (CQI) reports. A-HARQ also increases the number of RTX within a 4 ms time period, by utilising Transmission Time Interval (TTI) bundling to decrease the delay incurred from many RTX. A performance analysis is conducted, where A-HARQ was shown to have about 35% lower delay than the legacy HARQ, with a slight decrease in throughput, for low Signal-to-Noise (SNR) values.